Currently prescribed drugs in the UK that could upregulate or downregulate ACE2 in COVID-19 disease: a systematic review - Dambha-Miller, H; Absari, A; Hodgson, S; Wilcox, CR; Khan, S; Islam, N; Little, P; Griffin, SJ (BMJ Publishing Group, 2020)
Objective To review evidence on routinely prescribed drugs in the UK that could upregulate or downregulate ACE2 and potentially affect COVID-19 disease.